PERTUMBUHAN DAN HASIL TANAMAN GANDUM (Triticum aestivum L.) VARIETAS DEWATA DALAM POLYBAG PADA BERBAGAI POPULASI DAN KOMPOSISI MEDIA TANAM - Nugraheni Widyawati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
Studies on the growth and yield performance of wheat (Triticum aestivum L. variety of Dewata) planted in polybag with various populations and media compositions, had been conducted in Faculty of Agriculture Satya Wacana Christian University field research, located at Salaran – Kopeng village, Semarang district, from April 2012 to August 2012. Location of the study lies at an altitude of 900 meters above the sea level. Purpose of this study were to determine the appearance of both the growth and yield of wheat grown in polybag with a various population densities and media composition, as well as to determine the combination of treatments that producing the highest yield of wheat. Factorial design used that was consisted of two factors, i.e: (1) growing gedia composition with four different volume ratio of sand, soil and manure (1:1:1), (1:1:0), (1:0:1) and (0:1:1), and (2) population densities consisted of four: 1 seeds per polybag; 2 seeds per polybag; 3 seeds per polybag and 4 seeds per polybag, so that there were 16 combinations of treatments. Each combination was repeated three times. Basic design of the experiments used Randomized Block Design. Experimental data were analyzed by using analysis of variance (ANOVA) and high significant difference (HSD) test at 95% level of confidence. The conclusion of this study were: (1) Combination of treatment of population densities and composition of growing media influence on plant height, number of plants per cluster, panicle length, seed weight per panicle, seed weight per cluster and seed weight per polybag and (2) the highest seed weight per polybag was resulted in the density of population of 4 seeds per polybag and planting on mixed media of sand, soil and manure in the volume ratio of 1:1:1.